(untitled) (ACME, 2021)
More than ninety years after the second edition (1926-1928) of Jacob Wackernagel’s Vorlesungen über Syntax, some considerations are proposed on the famous Lectures of the “Sprachforscher philologischer Richtung” in Basel. The rereading in the light of developments in Indo-European linguistics reveals themes and cues with a strong impact on subsequent research, also allowing us to glimpse how the analysis of individual morphosyntactic phenomena does not lack a projection towards more general aspects.